Effect of low-dose ketamine on PerioperAtive depreSsive Symptoms in patients undergoing Intracranial tumOr resectioN (PASSION): study protocol for a randomized controlled trial - Yang Zhou (Trials, 2018)
Abstract Background Perioperative depressive symptoms (PDS) are common mental comorbidities that influence clinical outcomes and prognosis. However, there is no rapid-acting treatment to address these symptoms during a limited hospital stay. Methods/design This is a single-center, randomized, placebo-controlled, and double-blind trial. Randomization will be applied and stratified by the severity of PDS (moderate versus severe). Eighty patients who are scheduled for elective supratentorial brain tumor resection with PDS will be randomly allocated to the ketamine or placebo group with a ratio of 1 to 1. Patients in the ketamine group will be administered low-dose ketamine (0.5 mg/kg) intravenously for 40 min while the dural mater is being cut into, whereas patients in the placebo group will receive the same volume of normal saline at the same infusion rate at the same time points. The primary endpoint is the rate of PDS response at 3 days after surgery. Secondary outcomes include efficacy parameters such as the rate of PDS remission and safety outcomes such as the incidence of postoperative delirium, quality of recovery, and psychiatric side effects. Discussion This study aims to determine whether ketamine could improve the depressive symptoms of perioperative patients undergoing supratentorial brain tumor resection. It will also examine the safety of administering ketamine as an intraoperative anti-depressant. Trial registration ClinicalTrials.gov, NCT03086148. Registered on 22 March 2017.